2020
DOI: 10.1021/acssuschemeng.0c04378
|View full text |Cite
|
Sign up to set email alerts
|

Keratinase Biosynthesis from Waste Poultry Feathers for Proteinaceous Stain Removal

Abstract: This study is aimed at assessing the keratinase production related to industrial detergent applications from a newly isolated Bacillus cereus IIPK35. The production was optimized through submerged fermentation by a one-variable-at-a-time method, followed by the response surface methodology, using waste chicken feathers as a carbon source and resulted in a 5-fold increase in keratinase production in 48 h (103.79 U/mL) when supplemented with 1.43% w/v feather and other nutrients. Time-course study of 120 h revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…The optimal inoculum size differed from that of B. subtilis KD-N2 (10%) [ 29 ]. And our finding is similar to B. cereus IIPK35, whose inoculum size was 2% for high keratinase production [ 23 ]. Fermenting temperature usually influences the metabolism of microorganisms and exhibits a significant impact on the biosynthesis of target enzymes.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The optimal inoculum size differed from that of B. subtilis KD-N2 (10%) [ 29 ]. And our finding is similar to B. cereus IIPK35, whose inoculum size was 2% for high keratinase production [ 23 ]. Fermenting temperature usually influences the metabolism of microorganisms and exhibits a significant impact on the biosynthesis of target enzymes.…”
Section: Resultssupporting
confidence: 82%
“…Fermenting temperature usually influences the metabolism of microorganisms and exhibits a significant impact on the biosynthesis of target enzymes. In this study, the optimum growth temperature for keratinase production is 35 °C, which is similar to some other bacterial keratinases with an optimum temperature range of 30 to 40 °C [ 23 , 30 , 31 ]. The results indicated that B. cereus YQ15 belongs to mesophilic bacteria, exhibiting superior potential in industrial application than the thermophiles because of the less energy cost from this perspective.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The experimental data were fitted to a second-order polynomial equation through multiple regression analysis, and analysis of variance (ANOVA) indicated the competence of the model so obtained. Mutual interactions between the independent variables were characterized by three-dimensional response surface plots 29 .…”
Section: Methodsmentioning
confidence: 99%